2013
DOI: 10.1162/jocn_a_00441
|View full text |Cite
|
Sign up to set email alerts
|

Why Bilateral Damage Is Worse than Unilateral Damage to the Brain

Abstract: Human and animal lesion studies have shown that behavior can be catastrophically impaired after bilateral lesions but that unilateral damage often produces little or no effect, even controlling for lesion extent. This pattern is found across many different sensory, motor, and memory domains. Despite these findings, there has been no systematic, computational explanation. We found that the same striking difference between unilateral and bilateral damage emerged in a distributed, recurrent attractor neural netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
124
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(142 citation statements)
references
References 51 publications
16
124
2
Order By: Relevance
“…Of interest, this pattern took place in a context of mild semantic dysfunction that was evident in different types and modalities of semantic tasks, thus supporting the critical role of the left temporal pole for conceptual knowledge (Bruffaerts et al 2013;Clarke et al 2011Clarke et al , 2013Chan et al 2011;Mesulam et al 2013;Peelen and Caramazza 2012). It is important to highlight that, although current results demonstrate that unilateral damage to the left temporal pole can produce a significant semantic impairment, it is, however, far from the devastating degradation observed in semantic dementia and other bilateral conditions (Antonucci et al 2008;Lambon Ralph et al 2010a, 2012Lambon Ralph et al 2012;Schapiro et al 2013;Tsapkini et al 2011). PC was supported by a Ramon y Cajal Fellowship from the Spanish Ministry of Science and Innovation (RYC-2010-05748). CP was supported by Spanish Ministry of Science and Education (AP2009-4131).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Of interest, this pattern took place in a context of mild semantic dysfunction that was evident in different types and modalities of semantic tasks, thus supporting the critical role of the left temporal pole for conceptual knowledge (Bruffaerts et al 2013;Clarke et al 2011Clarke et al , 2013Chan et al 2011;Mesulam et al 2013;Peelen and Caramazza 2012). It is important to highlight that, although current results demonstrate that unilateral damage to the left temporal pole can produce a significant semantic impairment, it is, however, far from the devastating degradation observed in semantic dementia and other bilateral conditions (Antonucci et al 2008;Lambon Ralph et al 2010a, 2012Lambon Ralph et al 2012;Schapiro et al 2013;Tsapkini et al 2011). PC was supported by a Ramon y Cajal Fellowship from the Spanish Ministry of Science and Innovation (RYC-2010-05748). CP was supported by Spanish Ministry of Science and Education (AP2009-4131).…”
Section: Discussionsupporting
confidence: 64%
“…Overall, this pattern of word retrieval deficits occurring in conjunction with semantic paraphasias observed in the patients group is in line with the postulation of the 'no right to speak' model (Lambon Ralph et al 2001) that unilateral damage to left ATL generates some impairment of the semantic system (Antonucci et al 2008;Bell et al 2001), manifesting in a certain degree of anomia and semantically related naming errors (Bell et al 2001;Lambon Ralph et al 2012;Mesulam et al 2013;Tsapkini et al 2011). Therefore, current findings demonstrate that a restricted lesion to the left temporal pole, without the confounding effect of co-occurring damage to other regions of the temporal lobe (Mion et al 2010;Tsapkini et al 2011), or of different aetiologies (Jefferies and Lambon Ralph 2006;Noppeney et al 2007), can cause a significant deficit in object naming and in semantic function (Mesulam et al 2013), although less severe than that observed after bilateral damage (Antonucci et al 2008;Lambon Ralph et al 2012;Schapiro et al 2013). Furthermore, in the majority of the patients, the lesion was located in area TG, at the very rostral part of the temporal pole, which was the only subregion to show functional connectivity with all other subregions in the temporal pole, thus considered ''likely an important convergence hub'' (Pascual et al 2014).…”
Section: Discussionmentioning
confidence: 55%
“…Despite their large lesions, this impairment was moderate rather than severe, which probably should not be surprising: it is well known from both human and animal research that a unilateral lesion often results in restricted or even minimal cognitive impairment, whereas bilateral damage to the same region is more than twice as devastating (Heffner and Heffner, 1986 Q5 ;Scoville and Milner, 1957;Schapiro et al, 2013). With respect to the second issue, these two patients resembled SD in broad outline but differed in more detailed characteristics.…”
Section: Discussionmentioning
confidence: 88%
“…19). These and parallel neuropsychological data on left vs. right ATL differences have been formally considered in a number of implemented computational models of semantic processing (40,41). The key ideas from these models are that semantic representation may be supported by regions within the ATLs, bilaterally, with differential patterns of activation or impairments in unilateral ATL patients arising from the effects of asymmetric connectivity with input and output areas.…”
Section: Discussionmentioning
confidence: 99%